Classification of acquired lesions of the corpus callosum with MRI. - Friese, SA; Bitzer, M; Freudenstein, D; Voigt, K; Küker, W (2000)
MRI has facilitated diagnostic assessment of the corpus callosum. Diagnostic classification of solitary or multiple lesions of the corpus callosum has not attracted much attention, although signal abnormalities are not uncommon. Our aim was to identify characteristic imaging features of lesions frequently encountered in practice. We reviewed the case histories of 59 patients with lesions shown on MRI. The nature of the lesions was based on clinical features and/or long term follow-up (ischaemic 20, Virchow-Robin spaces 3, diffuse axonal injury 7, multiple sclerosis 11, hydrocephalus 5, acute disseminated encephalomyelitis 5, Marchiafava-Bignami disease 4, lymphoma 2, glioblastoma hamartoma each 1). The location in the sagittal plane, the relationship to the borders of the corpus callosum and midline and the size were documented. The 20 ischaemic lesions were asymmetrical but adjacent to the midline; the latter was involved in new or large lesions. Diffuse axonal injury commonly resulted in large lesions, which tended to be asymmetrical; the midline and borders of the corpus callosum were always involved. Lesions in MS were small, at the lower border of the corpus callosum next to the septum pellucidum, and crossed the midline asymmetrically. Acute disseminated encephalomyelitis and the other perivenous inflammatory diseases caused relatively large, asymmetrical lesions. Hydrocephalus resulted in lesions of the upper part of the corpus callosum, and mostly in its posterior two thirds; they were found in the midline. Lesions in Marchiafava-Bignami disease were large, often symmetrically in the midline in the splenium and did not reach the edge of the corpus callosum.